The role of phytochrome B1 of tomato (Solanum lycopersicum L.) in the reproductive stage during drought stress - Silva Junior, Carlos Alberto (2021)
Photoreceptors are primarily known as key photomorphogenic modulators of various physiological events during plant development. Although there are different groups of photoreceptors, the phytochrome B (phyB) family mediates developmental responses in a wide range of plant species, from seed germination to flowering. In addition, these molecules also regulate abiotic stress acclimation responses, such as salinity, drought, low/high temperature, high light, and heavy metals. The signalling pathways mediated by phyB could enhance plant resistance to environmental stresses, as phyB mutants reduced leaf transpiration through lowering of stomatal conductance, increased the antioxidant system, enhanced protective pigments, and increased the expression of genes related to plant stress acclimation. Therefore, the scope of chapter one is to compile and discuss the evidence on abiotic stress response in plants that are modulated by the phytochrome type B family. In addition, chapter two aimed to elucidate the responses mediated by phyB1 in tomato fruit production comparing the effects of drought stress in vegetative and reproductive stages. The water deficit treatment was performed in two different stages growth: in vegetative (start at 26 days after sowing [DAS]); end at 36 DAS) and reproductive (start at 33 DAS; end at 41 DAS) stage growth.